A Stable Silanol Triad in the Zeolite Catalyst SSZ‐70. Issue 27 (23rd April 2020) - Schroeder, Christian; Mück‐Lichtenfeld, Christian; Xu, Le; Grosso‐Giordano, Nicolás A.; Okrut, Alexander; Chen, Cong‐Yan; Zones, Stacey I.; Katz, Alexander; Hansen, Michael Ryan; Koller, Hubert
Abstract: Nests of three silanol groups are located on the internal pore surface of calcined zeolite SSZ‐70. 2D 1 H double/triple‐quantum single‐quantum correlation NMR experiments enable a rigorous identification of these silanol triad nests. They reveal a close proximity to the structure directing agent (SDA), that is, N, N′‐diisobutyl imidazolium cations, in the as‐synthesized material, in which the defects are negatively charged (silanol dyad plus one charged SiO − siloxy group) for charge balance. It is inferred that ring strain prevents the condensation of silanol groups upon calcination and removal of the SDA to avoid energetically unfavorable three‐rings. In contrast, tetrad nests, created by boron extraction from B‐SSZ‐70 at various other locations, are not stable and silanol condensation occurs. Infrared spectroscopic investigations of adsorbed pyridine indicate an enhanced acidity of the silanol triads, suggesting important implications in catalysis. Abstract : Silanol defects determine adsorption and catalysis in zeolites by their hydrophilic properties, but they can also contribute to catalytic reactions through their weak acidities or cooperative effects with other active sites. Well‐defined silanol defect clusters (see structure: cyan H, red O, black Si) with distinct size in topologically related zeolites, SSZ‐70 and ITQ‐1 are identified by NMR spectroscopy.